Cheap talk and secret intentions in a public goods experiment - Werner Güth; Maria Vittoria Levati; Torsten Weiland (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
In a public goods experiment, subjects can vary over a period of stochastic length two contribution levels: one is publicly observable (their cheap talk stated intention), while the other is not seen by the others (their secret intention). When the period suddenly stops, participants are restricted to choose as actual contribution either current alternative. Based on the two types of choice data for a partners and a perfect strangers condition, we confirm that final outcomes strongly depend on the matching protocol. As to choice dynamics, we distinguish different types of adaptations.
Keywords: C72; H41; D82; D83; 330; Public goods game; Cheap talk communication; Real-time protocol; Nichtkooperatives Spiel; Öffentliches Gut; Information; Kommunikation; Test